Keterkaitan Faktor-Faktor Organisasional, Individual, Konflik Peran, Perilaku Etis Dan Kepuasan Kerja Akuntan Manajemen - Muhammad Fakhri Husein (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2008)
This research develops a model for the linkage of organizational factors (role model, understanding code of ethics, and organizational commitment), individual factor (moral principle) to role conflict, ethical behavior, and their consequences to job satisfaction of management accountants in Indonesia. Using purposive sampling, this research is supported by 119 respondents. The response rate is 23,8%.To get a comprehensive view on antecedents of ethical behavior and role conflicts and their consequences to job satisfaction, this research is supported by management accountant respondents. Measurement of model is performed in analysis in Structural Equation Modeling by Analysis of Moment Structure (AMOS). Some indicators of goodness of fit model are still unsatisfactory, but this research confirms some hypotheses of the previous researches. Understanding Code of Ethics, organizational commitment and role model influence significantly ethical behavior of management accountants. Meanwhile, moral principle does not influence significantly ethical behavior of management accountants.Role conflict is not influenced significantly by understanding code of ethics and moral principle, but it is influenced significantly by organizational commitment and role model. Management Accountant job satisfaction is influenced significantly by ethical behavior but role conflict doesn’t influence significantly management accountant job satisfaction.